2002
DOI: 10.1152/jn.2002.88.4.1941
|View full text |Cite
|
Sign up to set email alerts
|

Response Selectivity for Species-Specific Calls in the Inferior Colliculus of Mexican Free-Tailed Bats is Generated by Inhibition

Abstract: Here we show that inhibition shapes diverse responses to species-specific calls in the inferior colliculus (IC) of Mexican free-tailed bats. We presented 10 calls to each neuron of which 8 were social communication and 2 were echolocation calls. We also measured excitatory response regions: the range of tone burst frequencies that evoked discharges at a fixed intensity. The calls evoked highly selective responses in that IC neurons responded to some calls but not others even though those calls swept through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 59 publications
(43 reference statements)
11
105
0
Order By: Relevance
“…The remaining 8% were tuned to frequencies above 30 kHz. Although most of the neurons in our sample were tuned to a narrow range of frequencies, between 21 and 25 kHz, this frequency range is overrepresented in the cochlea as well as in other auditory brainstem nuclei of Mexican free-tailed bats (Vater and Siefer, 1995;Bauer et al, 2002;Klug et al, 2002;Xie et al, 2005). A representative STRF is shown in Figure 2 A and illustrates many of the features common to the STRFs we obtained from the other 58 neurons.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The remaining 8% were tuned to frequencies above 30 kHz. Although most of the neurons in our sample were tuned to a narrow range of frequencies, between 21 and 25 kHz, this frequency range is overrepresented in the cochlea as well as in other auditory brainstem nuclei of Mexican free-tailed bats (Vater and Siefer, 1995;Bauer et al, 2002;Klug et al, 2002;Xie et al, 2005). A representative STRF is shown in Figure 2 A and illustrates many of the features common to the STRFs we obtained from the other 58 neurons.…”
Section: Resultsmentioning
confidence: 81%
“…One explanation for this difference in the effects of inhibition on direction selectivity and inseparability is that blocking inhibition frequently causes an expansion of the excitatory receptive field, in which the expansion is not uniform along the spectrotemporal axis (Yang et al, 1992;Palombi and Caspary, 1996;LeBeau et al, 2001;Klug et al, 2002). Such a nonuniform expan- 6.…”
Section: Inhibition Shapes Directional Selectivitymentioning
confidence: 99%
“…We used the pure tone response model as our reference because previous studies show that the IC is the first site in the ascending auditory pathway in which neural responses to vocalizations cannot be predicted by neural responses to pure tones alone Klug et al, 2002;Pollak et al, 2003). Our results showed that the mouse IC encodes vocalizations more efficiently than an encoding predicted by the pure tone model.…”
Section: Efficient Encoding In the Icmentioning
confidence: 85%
“…development ͉ response selectivity N eural selectivity for species-specific vocalizations is present in several vertebrate groups (1)(2)(3)(4)(5)(6)(7)(8). In songbirds, experience shapes the development of vocalization selectivity (9)(10)(11).…”
mentioning
confidence: 99%